2017
DOI: 10.1523/jneurosci.0649-17.2017
|View full text |Cite
|
Sign up to set email alerts
|

Overlapping Representation of Primary Tastes in a Defined Region of the Gustatory Cortex

Abstract: Both physiological and imaging approaches have led to often-disparate conclusions about the organization of taste information in gustatory cortex (GC). In this study, we used neuroanatomical and imaging approaches to delineate the likely area of insular cortex given to gustatory function and to characterize taste responses within this delineated area in female and male C57BL/6J mice. Anterograde tracers were injected into the taste thalamus (the medial parvicellular portion of the ventral posterior medial divi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
83
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(97 citation statements)
references
References 58 publications
13
83
1
Order By: Relevance
“…A total of 185 units were isolated across 10 sessions in 6 mice-4 mice received 2 sessions each (in the latter case sessions were recorded from separate DV locations in the GC; see material and methods). As shown in Figure 1, our recordings spanned much of the region (AP Bregma +1.6 to 0.0; DV 2.25 -3.25 mm from the surface of the brain) receiving input from taste thalamus (Chen et al, 2011;Fletcher et al, 2017) or from the amygdala (Matyas etal., 2014); prior work has shown this region to be important for taste behavior and learning in mice (Neseliler et al, 2011).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A total of 185 units were isolated across 10 sessions in 6 mice-4 mice received 2 sessions each (in the latter case sessions were recorded from separate DV locations in the GC; see material and methods). As shown in Figure 1, our recordings spanned much of the region (AP Bregma +1.6 to 0.0; DV 2.25 -3.25 mm from the surface of the brain) receiving input from taste thalamus (Chen et al, 2011;Fletcher et al, 2017) or from the amygdala (Matyas etal., 2014); prior work has shown this region to be important for taste behavior and learning in mice (Neseliler et al, 2011).…”
Section: Resultsmentioning
confidence: 99%
“…The above data suggest that GC taste neurons are broadly tuned "coarse coders," responding distinctly to multiple tastes; as such, they are consistent with previous reports of taste responses in rat GC (Yamamoto et al, 1985;Bahar et al, 2004;Fontanini and Katz., 2006;Jones et al, 2007;Piette et al, 2012;Samuelsen et al, 2013), and with calcium imaging data from mouse GC (Fletcher et al, 2017; but see Chen et al, 2011).…”
Section: Dynamics Of Taste-evoked Responses In Mice Gcmentioning
confidence: 99%
See 1 more Smart Citation
“…Accolla et al, 2007). For instance, Fletcher and colleagues (Fletcher et al, 2017) showed that neurons were preferentially tuned to specific tastes or combination of tastes; nonetheless such neurons were intermingled with neurons tuned to different tastes, in line with the notion of a non-topological gustatory organization in other species (for similar results in non-human primates, see Scott and Plata-Salamán, 1999).…”
Section: Introductionmentioning
confidence: 73%
“…and colleagues(Fletcher et al, 2017) also observed single taste preferences in the majority of neurons.Considering topological theories, we do not find any evidence for common maps across concentrations, though stable clusters were observed for single concentrations in line with previous research(Chen et al, 2011;Prinster et al, 2017). Moreover, we observed a patchy organization in insular cortex for different taste categories rather than a highly ordered topography(Chen et al, 2011;Prinster et al, 2017).…”
mentioning
confidence: 87%